A Determinant Expression for the Generalized Bessel Polynomials. (1st September 2013) - Yang, Sheng-liang; Zheng, Sai-nan
Abstract : Using the exponential Riordan arrays, we show that a variation of the generalized Bessel polynomial sequence is of Sheffer type, and we obtain a determinant formula for the generalized Bessel polynomials. As a result, the Bessel polynomial is represented as determinant the entries of which involve Catalan numbers.